DAMPAK PENGENAAN TARIF PAJAK PROGRESIF KENDARAAN BERMOTOR DI PROPINSI DKI JAKARTA - Eka Ermawati; Ni Putu Eka Widiastuti (InFestasi, 2014)
The purpose of this research is to examine empirically how the enforcement of a progressive tax rate impact on vehicle ownership for individuals on the territory of the province of DKI Jakarta. The source of data analysed is individual tax payers of motor vehicle owners who own vehicles of more than 1 unit and who are paying their tax in  Jakarta. There are 100 samples according criteria that can be processed toanswer hypothesis research. There is a significant relation-effect of progressive tax rates on taxpayers’ intention to do tax avoidance, with coefficient of determination of 42 %. It suggeststhat this tax rates can impact on the potential tax revenues in Jakarta but not affect taxpayers of four-wheeled vehicle owners. In other words,it reducesthe desire or motivation to buy a vehicle of more than 1 unit so that traffic jam fixed perceived.